Irish Fairy Tales - Stephens, James, 1882-1950; Rackham, Arthur, 1867-1939 (Salt Lake City, UT : Project Gutenberg, 2001)
"Irish Fairy Tales" by James Stephens is a collection of ten retellings published in 1920. Set in a wooded, medieval Ireland, these stories bring to life hunters, warriors, kings, and fairies from Irish mythology. Many tales follow the legendary Fianna and their captain, Fionn mac Uail, from the Fenian Cycle. Through magical transformations, epic quests, and encounters with fairy folk, Stephens weaves ancient folklore into vivid narratives where heroes face sorcery, seek wisdom, and navigate between the mortal world and Faery. (This is an automatically generated summary.)
The story of Tuan Mac Cairill -- The boyhood of Fionn -- The birth of Bran -- Oisi'n's mother -- The wooing of Becfola -- The little brawl at Allen -- The Carl of the drab coat -- The enchanted cave of Cesh Corran -- Becuma of the white skin -- Mongan's frenzy.
Wikipedia page about this book: https://en.wikipedia.org/wiki/Irish_Fairy_Tales
Release date is 2001-11-01
Produced by A. Elizabeth Warren, and David Widger
Keywords: Tales -- Ireland; Folklore -- Ireland; Fairy tales -- Ireland